Technological Acceleration, Ageing Process and COVID-19. The Role of Scientific Information between Opportunities and Limits. Results of an Empirical Research in Central Italy - Esposito, Maurizio; Romualdi, Iolanda (Italian Sociological Review, 2022)
In this article, the authors present the results of an empirical research regarding people over 65 years old living in Central Italy, that have contracted the Sars-CoV-2 virus. The choice of such target is strictly dependent on the need to investigate, specifically, how this category, in a risky situation, was able to deal with the illness and cope with the whole condition; both in relation to the management of health and governmental information, and in relation to the use of information channels and technological devices. Through a research carried out with qualitative methodology, a series of analysis emerged around: 1) the idea of promoting and ensuring digital literacy with a view to the social innovation to cope with the risks of ‘infodemic’; 2) the urge to reflect on the necessity of keeping active and constant the dialogue between scientific community and user/citizen in the view of a transfer of knowledge and techno-scientific information, especially in periods of health crisis, in order to mitigate the effects due to digital divide; 3) the need to analyze the life of older people in a context of indeterminacy and fear in which social habits and consolidated certainties have been subjected to a totalizing tension.